Rheology in Wood Engineering. (2015) - Curtu, Ioan; Stanciu, Mariana Domnica; Dates, Rodica
Abstract: The system strains under external loads in a certain amount of time and under the influence of the environmental factors define the rheological behavior. Rheological phenomena depend on many factors: temperature such as air humidity or moisture content of rheological system, radiations in term of intensity, duration, type - UV, IR, X, geometry of the parts; loadings in terms of intensity, variation, duration; defects; aggressive environment; composition, material properties; combinations of these factors. Rheology science is based on the theories of the strength of materials, thermodynamics, chemistry and materials science, but in terms of application, it provides a personalized analysis or diagnosis according to the condition of the structures/systems used. Wooden constructions are subjected to various loadings on both short and long durations. The joints can be elastic (flexible) if the failure occurs gradually, or plastic, if the failure occurs suddenly. Sudden failure of joints is caused by shear as predominant load because wood does not resist at shear stresses. In order to study the rheological behavior of the wood joints with metal rods under constant load, three types of joints in terms of diameters of bolts and stiffening systems were tested. They were stressed to traction force of 500 to 900 N for 200 days, in real conditions of temperature (-7 °C la +30 °C) and humidity (from 47.8% to 83.8%). The aim of the tests were to determine the rheological behavior of wooden joints; variation of deformations in relation to the relative humidity and temperature; rate of strain and connections in determining rheological model of wood with threaded rods. It was found that the low temperatures during winter (-7…0 °C) correlated with high relative humidity led to sudden changes in strain. It was observed that the high-speed deformation had a joint with the largest diameter rod (8 mm). The paper highlights the rheological analysis of joints in wooden rods in real conditions of temperature and humidity, with regards to applied tension and the determination of the creep function that characterizes these types of connections, establishing the optimum diameter rods.